2020
DOI: 10.3389/fpls.2020.00828
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Better Understanding of Genotype × Environment × Management Interactions—A Global Wheat Initiative Agronomic Research Strategy

Abstract: Beres et al.A Global Agronomic Research Strategy countries representing a large proportion of the wheat grown in the world. The yield gap analysis and research database positions the EWG to influence priorities for wheat agronomy research in member countries that would facilitate collaborations, minimize duplication, and maximize the global impact on wheat production systems. This paper outlines a vision for a global WI agronomic research strategy and discusses activities to date. The focus of the WI-EWG is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 40 publications
(42 reference statements)
0
39
0
Order By: Relevance
“…Moreover, management practices are often borrowed from research conducted on common wheat. While we have sought to present synergies possible with a G × E × M paradigm, it is clear a coordinated effort and cross-disciplinary approach is yet to be fully realized, which underscores the need for transformational research that exemplifies the G × E × M paradigm (Beres et al, 2020). In many areas of the world, climate change will drive future research and innovation, which requires a re-think of how we link together all the genetic and management components when designing a resilient cropping system (Fletcher et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, management practices are often borrowed from research conducted on common wheat. While we have sought to present synergies possible with a G × E × M paradigm, it is clear a coordinated effort and cross-disciplinary approach is yet to be fully realized, which underscores the need for transformational research that exemplifies the G × E × M paradigm (Beres et al, 2020). In many areas of the world, climate change will drive future research and innovation, which requires a re-think of how we link together all the genetic and management components when designing a resilient cropping system (Fletcher et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…At present, breeders and agronomists largely work as a sequential tag team, or independently, conducting empirical research and making predictions to seek answers for the pressing questions within their own domains (e.g. Reynolds 2010 ; Fischer et al 2014 ; Cooper et al 2014b ; Assefa et al 2018 ; Edreira et al 2018 ; Beres et al 2020 ; Rotili et al 2020 ; Snowdon et al 2020 ). Proposals to accelerate improvement of crop productivity to account for the effects of climate change have largely ignored the influences of G × E × M interactions, or have assumed that the traditional research sequence of breeding for improved adaptation followed by agronomic optimisation will be effective for our future agricultural systems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A number of other studies have described the importance of G × E × M interactions and their contributions to crop yield productivity (Cooper et al 2001 ; Duvick et al 2004 ; Messina et al 2009 ; Hatfield and Walthall 2015 ; Beres et al 2020 ; Peake et al 2020 ; Rotili et al 2020 ; Snowdon et al 2020 ). Beyond the hybrid-by-density maize example above, a few studies have demonstrated effective improvement and utilisation of positive G × M interactions: improvement of sorghum yield for drought-prone environments in Australia (Hammer et al 2014 , 2020 ; Rodriguez et al 2018 ); improvement of wheat for drought-prone and irrigated environments in Australia (Hunt et al 2019 ); and improvement of maize hybrids for drought-prone environments of the US corn-belt by targeting selection for traits contributing to effective water use (Messina et al 2009 , 2018 ; Cooper et al 2014a , Gaffney et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustainable improvement of on-farm crop yield productivity, through improving yield potential and yield stability, is a complex long-term objective for both breeders and agronomists (Duvick et al, 2004;Hall and Richards, 2013;Fischer et al, 2014;Hatfield and Walthall, 2015;Beres et al, 2020;Cooper et al, 2021;Hunt et al, 2021). Heterogeneity of current environmental conditions that impact crop yield and the influences of climate change continually challenge the definition of the Target Population of Environments (TPE) for both breeders and agronomists (Chapman et al, 2012;Harrison et al, 2014;Lobell et al, 2015;Voss-Fels et al, 2019;Hammer et al, 2020;Cooper et al, 2021;Smith et al, 2021).…”
Section: Introductionmentioning
confidence: 99%